International competition, slim firms and wage inequality - Klaus Waelde; Pia Weiss (Center for Economic Studies and ifo Institute (CESifo), 2004)
A country with Cournot competition and free entry experiences an increase of its market size either due to economic growth or international integration of goods markets. The implied increase in competition leads to shrinking mark-ups and forces firms to reduce overhead costs relative to output. This implies a reallocation at the aggregate level from administrative to productive activities. Relative factor rewards change and wage inequality increases. The factor losing in relative terms can even lose in real terms. From a quantitative perspective, international competition is shown to be the more plausible cause of rising wage inequality.
Keywords: F12; J31; 330; international trade; wage inequality; foreign competition; free entry and exit; Internationaler Wettbewerb; Duopol; Lean Production; Lohnstruktur; Theorie